Failure to launch: aberrant cumulus gene expression during oocyte in vitro maturation. Issue 3 (March 2017) - Brown, Hannah M; Dunning, Kylie R; Sutton-McDowall, Melanie; Gilchrist, Robert B; Thompson, Jeremy G; Russell, Darryl L
Abstract : In vitro maturation (IVM) offers significant benefits for human infertility treatment and animal breeding, but this potential is yet to be fully realised due to reduced oocyte developmental competence in comparison with in vivo matured oocytes. Cumulus cells occupy an essential position in determining oocyte developmental competence. Here we have examined the areas of deficient gene expression, as determined within microarrays primarily from cumulus cells of mouse COCs, but also other species, between in vivo matured and in vitro matured oocytes. By retrospectively analysing the literature, directed by focussing on downregulated genes, we provide an insight as to why the in vitro cumulus cells fail to support full oocyte potential and dissect molecular pathways that have important roles in oocyte competence. We conclude that the roles of epidermal growth factor signalling, the expanded extracellular matrix, cumulus cell metabolism and the immune system are critical deficiencies in cumulus cells of IVM COCs.